Maiasaura (Dinosauria: Hadrosauridae) Tibia Osteohistology Reveals Non-annual Cortical Vascular Rings in Young of the Year - Woodward, Holly N. (Frontiers in Earth Science, 2019)
Annually, tetrapod vertebrate bone apposition is briefly interrupted, which typically coincides with the yearly environmental nadir. The temporary appositional hiatus is histologically recorded in bone cortex as a hypermineralized ring termed a line of arrested growth (LAG). One paleohistology study used this known LAG periodicity to quantify ontogenetic ages and growth rates in a dataset of fifty tibiae from the hadrosaurid dinosaur Maiasaura. In addition to LAGs, unusual cortical rings resulting from localized changes in vascular diameter were also noted in the tibiae, but not investigated further. The fifty Maiasaura tibiae from that study were histologically reexamined here to explore and document the composition, frequency, and cortical extent of localized vascular changes (LVCs) to assist with the recognition of similar structures in the cortices of other extinct taxa. This assessment reveals that the Maiasaura LVC is comprised of one or more laminae of primary osteons forming a ring of vascular canal diameters either uniformly larger or smaller than those of primary osteons adjacent to the vascular ring. With one exception, LVCs are only found prior to the first LAG in Maiasaura. However, LVC frequency is variable, ranging from specimens with no LVCs to as many as five prior to the first LAG. Because of their inconsistent frequency and restricted location within the cortex, LVCs likely do not have an annual periodicity in Maiasaura. Instead, LVCs may signal times of temporary but repeated stress. As both growth rates and mortality rates were highest during the first year in Maiasaura, illness or starvation seemed to have the greatest impact on growth during that time. A subadult tibia presenting with a pathologic directional cortical outgrowth is the only instance within the sample in which LVCs were found beyond the first LAG. Unfortunately, LVCs are under-explored in extant taxa, so the underlying cause(s) for Maiasaura LVCs cannot be established. As LVCs may provide yet another histological method for interpreting extinct vertebrate biology, foundational investigations of LVCs in extant vertebrates should be pursued.